Territorializing Aquatic Biodiversity: Local Ecological Knowledge (LEK) and Elasmobranch Distribution in the Kango Estuary (Gabon) - Mendene, Teddy Tanguy Mbeng; Kema Kema, Judicael Regis; Okanga Guay, Marjolaine; Akendengue Aken, Igor; Minko Youri, Mvomo; Kema Kema Nkollo, Aganga Christy Achtone (European Scientific Journal, ESJ, 2025)
Elasmobranchs (sharks and rays) are ecologically and socio-economically important, yet their distribution in Central African estuarine systems remains poorly understood. This study investigates the spatial and seasonal distribution of elasmobranchs in the Komo Estuary (Kango, Gabon) using Local Ecological Knowledge (LEK) collected through semi-structured interviews with 30 artisanal fishers, complemented by participatory mapping and GIS analyses. Four focal species were identified: Fontitrygon ukpam, F. margaritella, Carcharhinus leucas, and Sphyrna lewini. Among them, F. ukpam was the most widespread and abundant, extending from estuarine to upstream freshwater zones, whereas C. leucas and F. margaritella were concentrated in hot, saline lower-estuary waters. S. lewini was rarely reported. No statistically significant differences were detected between wet- and dry-season assemblages, although the data suggest a descriptive tendency toward slightly higher richness during the dry season. Temperature and salinity emerged as primary abiotic drivers, while prey availability, turbidity, and fishing pressure likely modulated these patterns. Spatial analyses (Kernel Density Estimation, Moran’s I, LISA, Getis-Ord Gi*) revealed localized hotspots and species aggregations not detectable through conventional surveys, underscoring the potential of LEK as a robust spatial dataset. Beyond documenting ecological distributions, fisher knowledge reflects lived territorialities, linking species ecology with social appropriation of aquatic environments. This research demonstrates the dual ecological and geographical value of LEK, contributing to biogeography by clarifying species–environment relationships, and to environmental geography by showing how local practices shape spatial perceptions of biodiversity. It also identifies priority estuarine sectors for monitoring and co-management in data-poor tropical systems.